PEMBERDAYAAN REMAJA DALAM UPAYA SADAR BEBAS THALASEMIA (SABET) - Fatchurrozak Himawan; Suparjo Suparjo; Gayuh Siska Laksanano (UNIVERSITAS BHAMADA SLAWI, 2022)
ABSTRACT Until now, thalassemia can not be cured and some of them require blood transfusions for life. However, we can prevent the occurrence of Thalassemia Major by preventing the occurrence of marriages between fellow carriers of Thalassemia trait. One way to support these efforts is to increase public knowledge and awareness followed by early detection efforts. Problems with thalassemia minor and intermediate sufferers are carriers or carriers of genes that are not realized by the public that can trigger an increase in thalassemia, public ignorance about this non-communicable disease of thalassemia needs to be done with education to increase awareness of the importance of early detection of thalassemia. The method used is education and mentoring of adolescents as role models and change agents in the community to increase awareness through education, evaluation is carried out by using a questionnaire to see the knowledge and attitudes of adolescents towards thalassemia. Results A volunteer team was formed from the students and youth of the standby village, Debong Kulon sub-district as SABET (Thalassemia-Free Awareness) educators. Conclusion: the delivery of information and education by students and youth in the village of standby, debong kulon village, shows that more than 80 percent of the knowledge and community have knowledge and attitudes that support the prevention of thalassemia. ABSTRAK Sampai saat ini penyakit Talasemia belum bisa disembuhkan dan beberapa jenis diantaranya memerlukan transfusi darah seumur hidup. Namun demikian, kita dapat mencegah terjadinya Talasemia Mayor dengan cara mencegah terjadinya pernikahan antar sesama pembawa sifat Talasemia. Sebagai salah satu cara mendukung upaya tersebut adalah dengan meningkatkan pengetahuan dan kesadaran masyarakat yang diikuti dengan upaya deteksi dini. Permasalahan penderita thalassemia minor dan intermediate merupakan carier atau pembawa sifat gen yang tidak disadari oleh masyarakat dapat memicu peningkatan thalasemia, ketidaktahuan masyarakat tentang penyakit tidak menular thalassemia ini perlu dilakukan dengan edukasi untuk meningkatkan kesadaran pentingnya deteksi dini thalassemia. Metode yang digunakan adalah Edukasi dan pendampingan remaja sebagai role model dan change agent di masyarakat untuk meningkatkatkan kesadaran melalui edukasi, evalasi dilakukan dengan sebaan kuesioner untuk melihat pengetahuan dan sikap remaja terhadap thalsemia. Hasil Terbentuk tim relawan dari mahasiswa dan remaja desa siaga kelurahan debong kulon sebagai educator SABET (Sadar Bebas Thalassemia). Kesimpulan: Penyampain informasi dan edukasi oleh mahasiswa dan remaja desa siaga kelurahan debong kulon menunnjukkan pengetahuan dan masyrakat lebih dari 80 persen memiliki pengetahuan dan sikap yang mendukung terhadap pencagahan thalsemia. Kata Kunci : Edukasi, Remaja, Thalasemia